PENGARUH PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE “GIVING QUESTION AND GETTING ANSWERS“ TERHADAP HASIL BELAJAR DASAR-DASAR KELISTRIKAN SISWA DI KELAS X TEKNIK AUDIO VIDEO SMK NEGERI 1 BUKITTINGGI - Gladiska Yunis; Yasdinul Huda; Dedy Irfan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
The problem in this research is the fact that found in SMK N 1 Bukittinggi, there are many students of class X Audio Video Engineering  is result study of learning outcomes below the minimum standard (KKM) in the subject Fundamentals of electricity at school set is set 75. Total students that are under KKM 60.35% and students those are above KKM 39.65%. Many factors that affect it, those are internal factors and external factors, as well as the learning model. This study aims to prove the existence of differences in learning outcomes using learning Active Learning Model Type "Giving Question and Getting Answers " with direct instructional model (MPL).  This study uses a Quasi Experimental Design, this study population is a class X student of SMK N 1 Bukittinggi TAV academic year 2013/2014. Sample technique done by randomly. Experiment class is a class that is treated by using the Active Learning Model Application Effects of Learning Type "Giving Question and Getting Answers " and that becames the control group is a class that uses MPL. Data of achievement test in the form of 20 questions about the essay. Data obtained from the analysis of the data manually to test for normality, homogeneity, hypothesis testing, research test results obtained from the average value of students learning model that uses Active Learning Type "Giving Questions and Getting Answers" is 79.53 while students are using the MPL amounting to 60.78. The result of the hypothesis by using the formula manually found that tcount 9.886> 2.35 ttable altenative hypothesis (H0) is rejected and (H1) is accepted. That means, significantly the average experimental class learning outcomes greater than the average of the control class learning outcomes. Keywords: Learning Active Learning model type "Question Giving and Getting   Answers",   MPL, Control and Experiment